Implementing Family Counseling Education to Resolve Domestic Conflict - Ferdinan Leonadus Lopo (Civiliza Publishing, Indonesia., 2026)
From an educational and psychological perspective, the family is expected to be the primary environment providing love, protection, and the formation of values and character for each family member. This study aims to determine the implementation of family counseling in handling domestic conflict in Bello Village, Kupang City. This research method uses a qualitative method with a descriptive approach, with data collection techniques conducted through interviews with married couples experiencing domestic conflict, counselors, and local community leaders. The results of the study indicate that domestic conflict is generally caused by a lack of effective communication, economic problems, differences of opinion in childcare, and interference from the extended family. The implementation of family counseling is carried out through the stages of problem identification, improving communication, providing assistance, and evaluating family relationships. The results of the study indicate that family counseling has a positive impact in reducing the intensity of conflict, improving interpersonal communication, and creating more harmonious family relationships. However, the implementation of family counseling still faces obstacles such as low public understanding of counseling services and social stigma. Therefore, it is necessary to increase socialization and strengthen family counseling services as a preventive and curative effort to maintain household harmony.